Design and implementation of parallel bioinformatics algorithms on heterogeneous computing architectures - Liu, Yongchao. (2012)
Massively parallel DNA sequencing technologies have revolutionized genomics and molecular biology by producing large volumes of high quality DNA sequence data at a relatively low cost. However, this growthin sequence data establishes the need for more powerful computational hardware infrastructure and more sophisticated software algorithms for efficient management and analysis. This poses a number of challengesto the bioinformatics community in order to meet the compute-intensive and data-intensive requirements of current sequence analysis.